Analisis Strategi Pemasaran Syariah Dalam Meningkatan Minat Beli Produk Abon Ikan - Toto Sukarnoto; Tarjono Tarjono; Nur Fauziyyah (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2023)
This study aims to determine sharia marketing strategies in increasing consumer buying interest in shredded catfish products at Winny Shredded Fish Sukapura-Cirebon. In this study, the method used is a qualitative method with a descriptive study. Qualitative research is research that describes current events, and describes these images, systematically and relates to the phenomenon being studied. This method seeks to present data and facts about the analysis of strategies to increase consumer buying interest in shredded catfish products at Winny Shredded Fish Sukapura-Cirebon by way of observation, in-depth interviews, documentation and triangulation. The subjects studied were owners, marketing, and consumers of Winny Shredded Fish. Based on the results of the research, the sharia marketing strategy in increasing consumer interest in buying shredded catfish products at Winny Shredded Fish Sukapura-Cirebon applies a word of mouth system with door to door and online marketing with a 4p marketing strategy. The sharia marketing strategy in increasing consumer buying interest for shredded catfish products at Winny Shredded Fish Sukapura-Cirebon has been quite good by applying the characteristics of sharia marketing, it has been proven that it already has many customers and agents as well as resellers in the Cirebon area and outside the city of Cirebon.Keywords : Marketing, Interest, Shrdded and Catfish Abstrak Penelitian ini bertujuan untuk mengetahui strategi pemasaran syariah dalam meningkatkan minat beli konsumen produk abon ikan lele di Winny Abon Ikan Sukapura-Cirebon. Dalam penelitian ini, metode yang digunakan adalah metode kualitatif dengan studi deskriptif. Penelitian kualitatif adalah penelitian yang menggambarkan peristiwa masa sekarang, dan mendeskripsikan gambaran tersebut, secara sistematis dan berhubungan dengan fenomena yang diteliti. Metode ini berusaha menyajikan data dan fakta-fakta tentang analisis strategi meningkatkan minat beli konsumen produk abon ikan lele di Winny Abon Ikan Sukapura-Cirebon dengan cara observasi, wawancara mendalam, dokumentasi dan triangulasi. Subjek yang diteliti yaitu owner, pemasaran, dan konsumen Winny Abon Ikan. Berdasarkan hasil penelitian, strategi pemasaran syariah dalam meningkatkan minat beli konsumen produk abon ikan lele di Winny Abon Ikan Sukapura-Cirebon ini menerapkan sistem word of mounth dengan dor to dor dan pemasaran lewat online dengan strategi pemasaran 4p. Strategi pemasaran syariah dalam meningkatkan minat beli konsumen produk abon ikan lele di Winny Abon Ikan Sukapura-Cirebon sudah cukup baik dengan menerapkan karakteristik marketing syariah terbukti sudah memiliki banyak pelanggan dan agen-agen juga reseller di wilayah Cirebon dan diluar kota Cirebon. Kata kunci : Pemasaran, Minat, Abon dan Ikan lele